2021
DOI: 10.1071/an20133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium supplementation on productive performance and antioxidant status of broilers under heat stress: a meta-analysis and a meta-regression

Abstract: Heat stress and a high metabolic rate of broilers increase the production of reactive oxygen species, which must be removed by antioxidants to prevent oxidative stress. Selenium (Se) is a potent antioxidant as it is a structural part of glutathione peroxidase (GPx). Dietary supplementation of Se can help reduce the oxidative stress caused by heat-stress conditions. The aim was to evaluate the effect of Se supplementation on the performance and antioxidant status of broilers under heat stress, by using a meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Adding appropriate Se levels to the diet can promote the growth and development of animals (Zhang et al, 2020a). Zepeda-Velazquez et al (2020) reported that Se supplementation improved the antioxidant status and productive performance of broilers under heat stress. Oral Se supplementation in dairy cattle was shown to improve Se milk levels (Ceballos et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Adding appropriate Se levels to the diet can promote the growth and development of animals (Zhang et al, 2020a). Zepeda-Velazquez et al (2020) reported that Se supplementation improved the antioxidant status and productive performance of broilers under heat stress. Oral Se supplementation in dairy cattle was shown to improve Se milk levels (Ceballos et al, 2009).…”
Section: Introductionmentioning
confidence: 99%